Education Problem and Profesionalisation of Human Resources - Sumardi, Vinsensius (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
The reality proves that Indonesianeducation always encounters problems. The problems which are commonly discussed arepertaining to quality, relevance and competitiveness. Hence, it is no wonder that quality of Indonesianeducation is lower than other neighbouring countries in Southeast Asean region, instead of relevanceand competitiveness. Another case that makes the condition worse is the higher level of unemployment.These problems need to be appropriately resolved. This writing attempts to offer the concept of humanresource development through professionalism of teachers and administrators as the way-out of copingwith the problem.Keywords: education, profesionalisation and human resource